Bioactive Ceramic Composites: A Dual Approach to Controlled Fluoride Delivery and Mechanical Reinforcement - Abdulmoneim Kazuz; Eman Naas; Ibratim Etbeni; Fathi Elhadi; Ahmed Albakouri (AlQalam Journal of Medical and Applied Sciences, 2025)
This study investigates the development of α-tricalcium phosphate (α-TCP) composite cements modified with 7.5 wt% fluorapatite (FAp) to enhance their functional performance for potential dental and orthopedic applications. The composites were designed to simultaneously achieve sustained fluoride ion release and improved structural properties. Fluoride release kinetics were evaluated using ion-selective electrodes in a standard fluoride solution over seven days, while mechanical performance was assessed through compressive strength testing after immersion in simulated body fluid (SBF) for 0, 3, and 10 days. Results reveal a sustained release, consistent with diffusion from a dual-phase reservoir. Compressive strength analysis showed progressive strengthening of the composite, but with a significantly slower increase in the FAp-containing composite compared to pure α-TCP. This behavior suggests that while FAp enhances long-term bioactivity through controlled ion delivery, it may also modulate the dissolution–reprecipitation pathway of α-TCP conversion into hydroxyapatite, thereby delaying early mechanical maturation. Overall, these findings demonstrate that fluorapatite incorporation into α-TCP matrices enables the design of multifunctional biomaterials with tunable ion release and mechanical evolution, offering a promising pathway for next-generation regenerative cement technologies.